Anh văn chuyên ngành thủy sản - Trần Thị Ngọc Bích (Trường Đại học Trà Vinh, 2020)
Chapter 1: Introduction. Chapter 2: Fish farming and culture systems. Chapter 3: Crustacean and culture systems. Chapter 4: Mollusks or moluccas and their culture systems. Chapter 5: Hatchery techniques and nutrients. Chapter 6: Environment and disease in aquaculture. Chapter 7: New techniques in aquaculture.